WORLD LITERATURE (Modern education and development, 2025)
World literature is an integral part of human culture and history, expressing the thoughts, emotions, and life experiences of various peoples. It consists of a collection of works created worldwide and encompasses a rich diversity of literary genres, forms, and styles. Studying world literature enables individuals to better understand the cultures and traditions of other nations and broadens their worldview.